Evaluation of the physiological responses to a 20-minute workout on the Cross-X machine - Shatzer, Jenna (My University, 2009)
The Cross-X is an exercise modality being marketed as an effective tool for toning the legs and buttocks, as well as providing a cardiovascular workout. The purpose of this study was to examine the physiological responses of a 20-minute workout on the Cross-X machine. Subjects (N=16) performed a maximal treadmill exercise test and two separate sessions on the Cross-X. The first session was a 10-minute practice session to familiarize the subjects to the machine. The second session was a 20-minute workout along with the provided DVD that was separated into the Beginner portion and Intermediate portion. HR and %HRmax were significantly different (p<.05) between the Beginner and the Intermediate portions of the workout (106 bpm, 58% of HRmax and 113 bpm, 62% of HRmax, respectively). Also, ratings of perceived exertion were significantly different between the two portions of the workout (9.6 and 10.3, respectively). The results show that although the Cross-X workout did not meet all ACSM recommendations for a cardiovascular workout, it can still provide a sufficient cardiovascular workout for lower fit individuals.
Keywords: Exercise tests; Exercise -- Physiological aspects; Exercise -- Equipment and supplies